FAKTOR YANG MEMPENGARUHI PARTISIPASI PRIA DALAM PENGGUNAAN METODE KONTRASEPSI VASEKTOMI DI KECAMATAN PAYANGAN KABUPATEN GIANYAR - Dwintasari, Pande Putri; Mulyawan, Ketut Hari (ARCHIVE OF COMMUNITY HEALTH, 2019)
Vasectomy has high effectiveness as contraceptive method with minimum side effects. This study aims to identify factors that influence male participation on the use of vasectomy as contraceptive method in Payangan sub-district, Gianyar regency. Study design was observational analytic with case control design. Sampling technique was purposive sampling with total sample of 92 peoples, with 46 peoples each for both cases and controls groups. Bivarate analysis was using logistic regression with ?=0.05. The result showed that of the 92 samples, 26.9%, of male cases have high education, 65.22%, has good awareness, 56.52% admitted that health services are in close distance, and 73.91% has good supports from their wife. Meanwhile, among the control groups, 34.78% has high education, 19.57% has good awareness, 43.48% admitted that health services are in close distance, and 32.61% has good supports from health providers and 28.6% has good supports from their wife. The result showed three factors that have significant association with the selection of vasectomy as contraceptive method are level of awareness (p<0,001), support from health provide (p<0,001) and support from wife (p<0,001). Keywords : Vasectomy, Participation, Male.